(untitled) (Transport systems and technologies, 2018)
Proved the concept of using intelligent transport information system in the conduct of technical studies. The proposed approach to operating conditions to determine the influence of the main stages of processing the information received about the technical condi tion of the vehicle by means of information software, namely conducting identification of the vehicle in the surrounding space, monitors unsteady conditions; collect baseline data about the parameters of technical condition and position in space vehicle in operation; predicted parameters of the vehicle; performs authentication conditions; diagnose technical state collects messages and diagnostics data of the vehicle; verify that the actual condition of the vehicle obtained parameters and operating conditions and in the performance monitoring. Proposed in the paper system general information provision process monitoring parameters of technical condition of vehicles provides a complete collection and processing of information in real-time on-board information system monitor placed on the vehicle and the system of collecting information that works in conjunction with driver and transport infrastructure and roads based on the current state of the road, transport, climate conditions and technical installations in the process of comparison normative data and previous data control; reflects the situation in the area of vehicle movement and analysis in real time and on request; identifies emergency the state road; archiving monitoring results; develop recommendations for speeding in areas of vehicular traffic on the results of the analysis.